2021
DOI: 10.21608/edj.2021.80359.1673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bonding Substrates on Fracture Resistance of Thin and Ultra-thin Occlusal Veneers constructed using Different CAD/CAM Materials

Abstract: Objectives:The aim of this study was to compare the fracture resistance of thin and ultra-thin occlusal veneers constructed from glass ceramics and hybrid ceramics bonded to different bonding substrates after thermomechanical aging. Materials and Methods:A total of 96 extracted maxillary first premolars were used. The teeth were divided into three equal groups according to the bonding substrate/protocol: EN, IDS Dentin, DDS Dentin. Each group was further subdivided into two equal subgroups according to the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(108 reference statements)
1
4
0
Order By: Relevance
“…Therefore, these results are within the clinically accepted limit. Our results come in with agreement with some studies 22,40 , and disagreement with other research studies 24,[41][42][43] whom reported significant difference between the ceramic groups. These differences might be attributed to different testing variables such as bonding protocol, aging, and different testing parameter.…”
Section: Table 3 Comparison Among Different Failure Modessupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, these results are within the clinically accepted limit. Our results come in with agreement with some studies 22,40 , and disagreement with other research studies 24,[41][42][43] whom reported significant difference between the ceramic groups. These differences might be attributed to different testing variables such as bonding protocol, aging, and different testing parameter.…”
Section: Table 3 Comparison Among Different Failure Modessupporting
confidence: 66%
“…The Celtra Duo group showed also no statistical significant difference with different thicknesses (1 mm, 1.5 mm), this came with agreement with Abbas et al (2020) 45 . Other studies reported also that increasing the thickness of the occlusal veneers did not impact the fracture resistance 19,46 , while other reported differently 42,47 .…”
Section: Table 3 Comparison Among Different Failure Modesmentioning
confidence: 94%
“…Another factor which explains the difference could be the fluctuation in the bonding substrate. The fluctuation in the bonding substrate was evaluated by Elsayed [53] when comparing the compressive strength of thin and ultrathin occlusal veneers constructed from glass ceramics and hybrid ceramics, bonded to different bonding substrates. The author found that the immediate dentin sealing concept (immediate treatment of the freshly cut dentin after exposure by the bonding agent) showed the highest mean compressive strength followed by enamel and delayed dentin sealing.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings reported in the literature by Elsayed. (2021) (33) They examined the fracture resistance of hybrid ceramics attached to various bonding protocols and thin and ultra-thin occlusal veneers made of glass ceramics. Between bonding techniques, there was a statistically significant difference whereby immediate dentin sealing (IDS) exhibited the highest statistically significant mean fracture resistance, followed by enamel and finally delayed dentin sealing (DDS).…”
Section: Discussionmentioning
confidence: 99%